Discovery of potential causative mutations in human coding and noncoding genome with the interactive software BasePlayer. Issue 11 (November 2018) - Katainen, Riku; Donner, Iikki; Cajuso, Tatiana; Kaasinen, Eevi; Palin, Kimmo; Mäkinen, Veli; Aaltonen, Lauri; Pitkänen, Esa
Abstract Next-generation sequencing (NGS) is routinely applied in life sciences and clinical practice, but interpretation of the massive quantities of genomic data produced has become a critical challenge. The genome-wide mutation analyses enabled by NGS have had a revolutionary impact in revealing the predisposing and driving DNA alterations behind a multitude of disorders. The workflow to identify causative mutations from NGS data, for example in cancer and rare diseases, commonly involves phases such as quality filtering, case–control comparison, genome annotation, and visual validation, which require multiple processing steps and usage of various tools and scripts. To this end, we have introduced an interactive and user-friendly multi-platform-compatible software, BasePlayer, which allows scientists, regardless of bioinformatics training, to carry out variant analysis in disease genetics settings. A genome-wide scan of regulatory regions for mutation clusters can be carried out with a desktop computer in 10 min with a dataset of 3 million somatic variants in 200 whole-genome-sequenced (WGS) cancers. Here, the authors describe how to use BasePlayer, an interactive and user-friendly software that facilitates the identification of causative mutations from next-generation sequencing data.